Prevalence and Risk Factors of Metabolic Syndrome in Women with Polycystic Ovarian Syndrome - Zahra Wasim; Tahira Riaz; Sadaf Shafique; Ghana Shahid; Islam Bano; Huma Shehzadi (Journal of Liaquat University of Medical & Health Sciences, 2024)
Objective: To find out the prevalence and risk factors of metabolic syndrome among females presenting with polycystic ovarian syndrome (PCOS) in a tertiary care setting. Methodology: This cross-sectional study was performed at the Department of Obstetrics and Gynecology, The Combined Military Hospital (CMH), Rawalpindi, Pakistan, from January to December 2022. A total of 277 non-pregnant females aged 18-35 years and diagnosed with PCOS presenting in the outpatient department were analyzed. Metabolic syndrome was diagnosed according to the AHA/NHLBI (ATP III) definition, while PCOS was labeled as per Rotterdam consensus guidelines. Prevalence of metabolic syndrome and associated risk factors were noted. Results: In a total of 277 women with PCOS, the mean age was 27.4±5.6 years, while 149 (53.8%) women were aged between 18 and 25. The residential status of 189 (68.2%) women was rural. There were 81 (29.2%) women with PCOS who were found to have metabolic syndrome. Waist circumference ? 80 cm (p=0.0031), HDL cholesterol < 50 mg/dl (p<0.0001), triglyceride ? 150 mg/dl (p<0.0001), hypertension (p<0.0001) and fasting blood glucose (FBG) > 110 mg/dl (p<0.0001) were having significant association with the presence of metabolic syndrome. Conclusion: A high prevalence of metabolic syndrome was found among women with polycystic ovarian syndrome. Central obesity, hypertension and abnormal levels of FBG, triglyceride and high-density lipoprotein were found to have a significant association with MBS among women with PCOS.